Experimental Investigation for Enhancement of Heat Transfer Coefficient in Car Radiator by Using Multiwall Carbon Nanotube (MWCNT) Nanofluid - Peeraiah, M.; Rao, K. Nagamalleswara; Balakrishna, B. (Automotive Laboratory of Universitas Muhammadiyah Magelang in collaboration with Association of Indonesian Vocational Educators (AIVE), 2024)
Improving heat transfer coefficient is a significant subject of study in many engineering domains. The use of nanofluids in car radiators might boost the heat transfer coefficient. The current study investigates a car's radiator's heat transfer coefficient and thermal conductivity. The heat transmission parameters of a car radiator were analyzed for coolant mass flow rates ranging from 600 to 1200 liters/hour and nanofluid concentrations ranging from 0.2 to 0.8% by volume. The primary coolant was prepared by combining water and ethylene glycol in a 60:40% combination with multi-walled carbon nanotube nanoparticles. The coolant's input temperatures were varied between 30 °C and 80 °C by impinging an air jet into the car radiator through a hallow cone nozzle plate with and without spacing. The result demonstrates that the volume flow rate of coolant on the tube side increases considerably as the heat transfer coefficient increases. At a nanoparticle concentration of 0.8 vol. %, the nanofluid's total heat transfer coefficient is enhanced by 12% compared with the base fluid. The heat transfer coefficient is improved by 42.6% for 0.8% volume of MWNCT nanofluid without spacing of the hallow cone nozzle plate and by 51.9% with spacing of the hallow cone nozzle plate.